2003
DOI: 10.1080/10903120390936842
|View full text |Cite
|
Sign up to set email alerts
|

P Rehospital R Apid-Sequence I Ntubation : A P Ilot T Raining P Rogram

Abstract: This RSI training model can serve as a template for other agencies seeking to implement RSI. Limitations of this model include the availability of live animal labs and the expense of conducting the training. Intense medical director involvement has been key to the success of this prehospital RSI program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This, together with the overall first pass success rate of 87.9%, is among the higher end of such rates for non-physician RSI reported in the literature [2] , [7] , [8] , [9] , [10] . Only three studies involving paramedic RSI could be found with a higher success rate [2] , [9] , [10] . Only one of these reported a first-pass success rate, which was 81% [9] .…”
Section: Discussionmentioning
confidence: 51%
“…This, together with the overall first pass success rate of 87.9%, is among the higher end of such rates for non-physician RSI reported in the literature [2] , [7] , [8] , [9] , [10] . Only three studies involving paramedic RSI could be found with a higher success rate [2] , [9] , [10] . Only one of these reported a first-pass success rate, which was 81% [9] .…”
Section: Discussionmentioning
confidence: 51%
“…States that allowed DAI or another form of medication-assisted intubation were also found to have had varying requirements for certification and additional training. Intense medical director oversight has been cited as key to the success of a prehospital DAI program along with intense training including animal laboratories and live intubations in an operating room 31 . States that required medical director sign-off and ongoing training may benefit from further study to assess success rates compared with states without these requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indeed support the idea that, for example, rapid sequence induction before endotracheal intubation can safely be administered by paramedics in the field [19-22]. Invasive airway management requires sufficient training of personnel and immediate availability of appropriate salvage airway devices [23] and monitoring [24].…”
Section: Must Out-of-hospital Intubation Be Performed By a Physician mentioning
confidence: 99%